Antibiotic resistance in livestock, environment and humans: One Health perspective - Sriniwas Pandey; Hyunok Doo; Gi Beom Keum; Eun Sol Kim; Jinok Kwak; Sumin Ryu; Yejin Choi; Juyoun Kang; Sheena Kim; Na Rae Lee; Kwang Kyo Oh; Ju-Hoon Lee; et al. (Journal of Animal Science and Technology, 2024)
Antibiotic resistance (AR) is a complex, multifaceted global health issue that poses a serious threat to livestock, humans, and the surrounding environment. It entails several elements and numerous potential transmission routes and vehicles that contribute to its development and spread, making it a challenging issue to address. AR is regarded as an One Health issue, as it has been found that livestock, human, and environmental components, all three domains are interconnected, opening up channels for transmission of antibiotic resistant bacteria (ARB). AR has turned out to be a critical problem mainly because of the overuse and misuse of antibiotics, with the anticipation of 10 million annual AR-associated deaths by 2050. The fact that infectious diseases induced by ARB are no longer treatable with antibiotics foreshadows an uncertain future in the context of health care. Hence, the One Health approach should be emphasized to reduce the impact of AR on livestock, humans, and the environment, ensuring the longevity of the efficacy of both current and prospective antibiotics.